Efficacy of Data Security in Managing the Database of SIMMAG 3D System. (2017) - Jacyna, Marianna; Gołębiowski, Piotr; Szczepański, Emilian; Wasiak, Mariusz
Abstract: The basis of functioning of the systems from different industries are reliable data. They can be both input parameters for operation of individual modules and representation of their work results. Due to multitude of functions performed by these systems, number of necessary parameters is very big. The most convenient form for their storage and processing are database with implemented management system. This article presents how to manage database on example of IT system supporting area of logistics – SIMMAG 3D, prepared within framework of a project funded by the NCBR under the Program for Applied Research (PBS3). The aim of system is modeling of warehouse facilities in 3D, their visualization, spatial planning and evaluation of processes occurring in them, as well as placement of objects in logistics network. SIMMAG 3D system has modular structure and each module gets values from database. The flow of data between its elements was discussed. During flow of data can occur risk of access to them by unauthorized entities. This article analyzes database of SIMMAG 3D system in terms of data security against unauthorized access.